Immunogenity of Protein Extract from Salivary Gland of Anopheles aconitus in Malaria Endemic Area - Septiawan, Mahful; Budayatin, Budayatin; Wiyono, Hidayat Teguh; Senjarini, Kartika (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
Although malaria had ever been virtually eradicated from Indonesia but currently malaria is recognized as a serious re-emerging threat to public health. This disease is caused by malaria parasite which is transmitted to human host by Anopheles mosquitoes as main vector. It has been widely observed that saliva of mosquito that transmits disease contains several factors that could enhance pathogen infection. Therefore, it should be possible to control pathogen transmission by vaccinating the host against the molecule(s) in saliva that potentiate the infection. However, immunogenic specific component in mosquitoes vectors of Malaria has not yet been identified so far. The objective of this study are to analyze protein profile of SDS-PAGE and to know the immunogity the protein extract of salivary gland from potential vector of Malaria i.e. An. aconitus We used immunogenic reaction between salivary gland extract of these vectors against pool of human sera which were collected from endemic area. The reaction conducted by the dot-blot analyze. SDS-PAGE studies showed 15 major polypeptide bands of 284, 100, 84, 75, 66, 57, 53, 48, 45, 38, 33, 29, 15, 14, and 11 kDa. The dot-blot studies showed that the protein extract of salivary gland from An. aconitus are immunogenic.